The Role of Law in Addressing Racial Disparities in the Criminal Justice System: a Social Science Perspective - Noviyantho, Rino (Journal of Public Representative and Society Provision, 2023)
This research analyses the ethnic and religious discrimination that is evident in Indonesian Criminal Justice System drawing of Critical Race Theory and Intersectionality Matrix frameworks. By addressing and examining the Appellate Court of Indonesia’s rulings on the ethnic Chinese and Papuans this study shows that the law in Indonesia and does not act independently and objectively to dispense justice but is instead used as a tool to maintain the domination of the majority. The study further notes how legal developments arising from historicalraçial and colonial prejudices have continued to disadvantage the minorities up to this present generation. It also discussed the effect of public opinion and the media on the Judicature and showed how populism triggered by the media has a detrimental effect on the independence of the judiciary and the reproduction of bias present in society into the legal framework. In doing so, this study reveals how race and religion interact with political affiliation to create specific kinds of inequalities and ensuring that particular minorities receive severe legal penalties. The implications of these findings are far reaching thus requiring for legal reforms which should be more than merely cosmetic interventions. Based on the research, it is necessary to expand the use of intersectional approach in the legal field, improve the status of the judiciary, as well as raise the general accountability of media.